2014
DOI: 10.1371/journal.pone.0095962
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administration of Ethanol, Cocaine, or Nicotine Does Not Decrease the Soma Size of Ventral Tegmental Area Dopamine Neurons

Abstract: Our previous observations show that chronic opiate administration, including self-administration, decrease the soma size of dopamine (DA) neurons in the ventral tegmental area (VTA) of rodents and humans, a morphological change correlated with increased firing rate and reward tolerance. Given that a general hallmark of drugs of abuse is to increase activity of the mesolimbic DA circuit, we sought to determine whether additional drug classes produced a similar morphological change. Sections containing VTA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…2a and b). Prior experiments that implanted subcutaneous morphine pellets for chronic morphine exposure exclusively used male rodents [32, 33, 41]. Therefore, we tested the drug administration paradigm in both sexes, and found no significant difference in free morphine (nM/g mouse) in isolated blood serum (Fig.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…2a and b). Prior experiments that implanted subcutaneous morphine pellets for chronic morphine exposure exclusively used male rodents [32, 33, 41]. Therefore, we tested the drug administration paradigm in both sexes, and found no significant difference in free morphine (nM/g mouse) in isolated blood serum (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…For soma size studies, VTA confocal z-stack images were taken using Olympus Fluoview FV1000 (version 4.2) and digital color camera (Olympus DP72) using a 60x PlanApoN (NA 1.42) oil objective and scan speed of 8.0 μs/pixel, Kalman average 4, step size 0.42 μm (Michigan State University Center for Advanced Microscopy). Following confocal imaging, neurons expressing either eYFP or mCherry (fluorescent protein, FP) were reconstructed in three dimensions and the surface area was measured using image analysis software (Volocity 3D Image Analysis Software, RRID:SCR_002668) as described previously [32, 33, 41]. We observed robust co-localization of TH protein (IHC) and viral-mediated fluorescent labeling with very few TH-negative, FP-positive neurons in the posterior lateral regions of the VTA (paranigral, PN and lateral portion of the PN) consistent with previous studies [44].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical and emotional CSDS was performed as described above. Mice underwent intracardial perfusion with 4% paraformaldehyde one-hour following SI testing on D1, and brains were post-fixed for 24 hr, cryoprotected in 30% sucrose and stored at 4 °C, per standard procedures 15 , 46 , 47 . Brains were sectioned (coronal, 35 µm), and selected brain regions were identified according to Paxinos G 48 .…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the morphological and structural changes induced in the VTA after nicotine self-administration. While one study has shown that nicotine self-administration has no effect on the size of DA soma in VTA (Mazei-Robison et al, 2014), that study did not examine GABAergic input processes.…”
Section: Introductionmentioning
confidence: 98%